Plan of Seoul Olympic games facilities and the execution of the plans of green area and road network of Seoul City Planning - Park, Kwanghyun (International Planning History Society Proceedings, 2018)
By analyzing the changes in planning for facilities for the 1988 Seoul Olympic Games, focusing especially on green areas and road networks, this study aims to reveal the transformation of Seoul City, sparked by the Seoul Olympic Games. Most of the new competition venues for the Olympic games were built in the green areas in the Jamsil District and the Taenung District. In particular, the Jamsil District was able to support the development of two main Olympic venues by reclaiming land through the revetment of the Han River. The river was the defining feature for Seoul City Planning’s Olympic development plans, dictating the paths of the broad highways and bridges which follow and span its waters.